2005
DOI: 10.1177/002242940505300105
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Successful and Unsuccessful Strategies in Individual Sight-Singing Preparation and Performance

Abstract: High school singers ( N=198) individually sang two melodies from notation, with and without a 30-second practice opportunity. Overall accuracy scores were significantly higher with preparation time. The less accurate singers, however, did not benefit from practice time. Analysis of videoed tests indicated that high scorers tonicized (vocally established the key), used hand signs, sang out loud during practice, physically kept the beat, and finished practicing the melody within 30 seconds significantly more fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
29
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 12 publications
7
29
1
Order By: Relevance
“…This specific finding agrees with a number of studies, in which choristers with instrumental experience were found to be significantly more successful on sight-singing tests than choristers without instrumental experience (Casarow, 2002;Daniels, 1986;Demorest & May, 1995;Henry & Demorest, 1994;Killian & Henry, 2005). A possibly more intriguing result of this study, however, and different from the findings in the other studies, was that when the kinesthetic hand sign requirement was eliminated, both groups (with and without instrumental backgrounds) performed similarly; there was no statistical difference between them.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This specific finding agrees with a number of studies, in which choristers with instrumental experience were found to be significantly more successful on sight-singing tests than choristers without instrumental experience (Casarow, 2002;Daniels, 1986;Demorest & May, 1995;Henry & Demorest, 1994;Killian & Henry, 2005). A possibly more intriguing result of this study, however, and different from the findings in the other studies, was that when the kinesthetic hand sign requirement was eliminated, both groups (with and without instrumental backgrounds) performed similarly; there was no statistical difference between them.…”
Section: Discussionsupporting
confidence: 92%
“…Each measure was worth 2 points, 1 point for acceptable pitch accuracy and 1 point for acceptable rhythm accuracy. Other viable scoring approaches have assessed points on a per-note basis (Demorest, 1998;Demorest & May, 1995;Henry, 2001;Henry & Demorest, 1994;Killian & Henry, 2005). The scoring approach chosen for this specific study (note to note within the context of a measure) was an attempt to quantify a holistic and real-life picture of each participant's sight-singing skills.…”
Section: Figure 1 Sight-singing Examples a And Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivating strong cognitive relationships between aural and visual aspects of music is key to success in many standard Western school music activities (Killian & Henry, 2005;Sheldon, 1998). Skills in error detection, sight-singing, and music reading depend, at least in part, on development of those cognitive relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Common challenges in the dictation process are lack of time to process percepts, lack of repetitions of the melody, and lack of a silent environment during the task (Karpinski, 2000;Killian & Henry, 2005). Students taking dictation must learn to work quickly and accurately, and to develop strategies to overcome the interference of aural distractions.…”
mentioning
confidence: 99%